Nutrient utilization of late sown wheat (Triticum aestivum) on acid soil (Haplustaif) of Bihar plateau - VERMA, U N; PAL, S K; SINGH, M K; THAKUR, R; UPASANI, R R (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during winter season of 1994-96 to study the nutrient utilization of late sown wheat (Triticum aestivum L. emend.Fiori.& Paol.) in split-plot design on acid soil (Haplustalf) of Bihar plateau. Main-plot included 4 seeding time, viz moderately late (1 December), late (16 December), very late (1 January) and extremely late (16 January) and sub-plot consisted of 4 nutrient levels, viz N0 P0 K0 N40 P8.7 K16.6 ,N80 P17.5 K24.9 and N120 P26.2 K33.2 Moderately late planted wheat responded to N120 P26.2 K33.2 yielding 4 661 kg/ha grain and removed 173.44, 16.67 and 148.00 kg/ha N,P and K respectively with 60.28 % nutrient uptake efficiency. Similarly, late planted crop responded to N80 P17.5 K24.9 yielding 3.061 kg/ha grain and absorbed 123.33,9.67 and 95.21 kg/ha N, P and K respectively with 45.28 % nutrient uptake effioiency. Likewise very late planted wheat exhibited response only up to N40 P8.7 ,K16.6 gave 2 035 kg/ha grain and removed 76.90, 6.51 and 70.28 kg/ha N, P and K respectively with uptake efficiency of 34.39 %. However, extremely late planted wheat did not respond to fertilizer application. Nutrient-use efficiency gradually decreased either with subsequent delay in seeding or increasing nutrient level.